Addenda et corrigenda à P. Attinger, A propos de ak «faire» - Attinger, Pascal (Zeitschrift für Assyriologie und vorderasiatische Archäologie, 2018)
The reader will find here an extensive addenda et corrigenda to P. Attinger, A propos de ak «faire» (II), ZA 95 (2005) 208–275. Only expressions that were not yet recorded in ZA 95 and relevant additions (new attestations of rare expressions, important discussions) have been taken into account. On the other hand, we have refrained from making additions to well-known expressions and from recording instances which were epigraphically or semantically too uncertain.